MULTI-AGENT SIMULATION OF ATTACKS AND DEFENSE MECHANISMS IN COMPUTER NETWORKS - Kotenko, Igor (International Journal of Computing, 2014)
The paper considers the approach to investigation of distributed cooperative cyber-defense mechanisms against network infrastructure oriented attacks (Distributed Denial of Service, network worms, botnets, etc.). The approach is based on the agent-based simulation of cyber-attacks and cyber-protection mechanisms which combines discrete-event simulation, multi-agent approach and packet-level simulation of network protocols. The various methods of counteraction against cyber-attacks are explored by representing attack and defense components as agent teams using the software simulation environment under development. The teams of defense agents are able to cooperate as the defense system components of different organizations and Internet service providers (ISPs). The paper represents the common framework and implementation peculiarities of the simulation environment as well as the experiments aimed on the investigation of distributed network attacks and defense mechanisms.